Existential Humanism and Philosophical Poetics - Kačerauskas, Tomas (Problemos, 2004)
The article is devoted to the analysis of the humanism of Sartre and Heidegger. The human being of Sartre is a project of the freedom, the creative whole of the past and the future. The existence of Heidegger is a temporal project too. The recognition of the being to the death allows to enlarge this project. According to the author of the article the humanism is not separated from the poetical inspirations. The human being is recognized with help of the poetical figures (metaphors) and is created analogous to the poetical creation. This horizon does not remove the question of God in the human life.